(untitled) (Bangladesh Journal of Scientific Research, 2012)
Key words: Infant mortality; health seeking behaviour; urban area DOI: http://dx.doi.org/10.3329/bjsr.v24i2.10772 Bangladesh J. Sci. Res. 24(2):145-154, 2011 (December)